The role of skin-homing T cells in extrinsic atopic dermatitis. - Seneviratne, S; Black, A; Jones, L; Bailey, A; Ogg, G (2007)
BACKGROUND: T cells that express Cutaneous Lymphocyte-Associated antigen (CLA) have the potential of migrating to the skin, and are hypothesized to play a role in cutaneous atopic disease. AIM: To investigate the immune phenotype and cytokine responses to Der p 1 stimulation of CLA+ T cells in extrinsic atopic dermatitis (EAD). DESIGN: In vitro testing, with controls. METHODS: Peripheral blood mononuclear cells (PBMC) were obtained from EAD patients (n=27) and non-atopic healthy individuals (n=22). Phenotypic analysis of naive, CLA+ and non-CLA+ memory/effector CD4+ and CD8+ T cells used markers of cell activation, differentiation, adhesion, apoptosis and chemokine receptor expression. Cytokine responses in these cells were studied following Der p 1 stimulation. RESULTS: CLA+ T cells from EAD patients expressed significantly higher levels of CD25, HLA-DR, CD38, CD71, CXCR1, CXCR2 and lower levels of bcl2, CCR5, CCR7, CXCR3, and CD62L (p<0.05). DISCUSSION: In EAD patients, CLA+ T cells express increased levels of markers associated with activation, adhesion and apoptosis, show differences in the level of expression of differentiation markers and display a distinct chemokine receptor preference, compared with cells from healthy controls. These data suggest a significant role for CLA+ T cells in the pathogenesis of cutaneous atopic disease.